(untitled) - Nurul Akma Jamil; Lee Khuan; Ai Theng Cheong; Siti Mariam Muda (University of Ostrava, 2021)
Aim: The aims of this scoping review were to identify the type of available evidence and map rapidly the key concepts underpinning milk sharing research. Design: Scoping review. Methods: Initially, the Scopus, ScienceDirect and EBSCOhost databases were searched. The keywords used were "milk sharing," "expressed breastmilk donation," "peer," "online" and "internet" and a combination of the Boolean operators "AND" and "OR." The snowballing technique was used to identify grey literature. The inclusion criteria were citations in English and Malay languages focusing on milk sharing. The review selection was performed by two independent reviewers. Results: The search identified two theses and 23 journal articles from 2010 to December 2019 that varied in terms of subject areas, aims, and methodologies. The majority of studies included were conducted in Western countries. Key findings identified the emerging concept of shared breastmilk, characteristics of donor and recipient mothers, facilitating factors for milk sharing, an individual's perception versus informed decision and transparency, the perception of "breast is the best" versus a bottle feeding culture, stigma surrounding milk sharing, a lack of involvement of health care providers in decision-making, problems with accessing human milk from the milk bank, and conflicting issues from a religious perspective. Conclusion: Milk sharing is a relatively contemporary infant feeding practice that raises several important issues. However, the existing literature is limited to the exploration of milk sharing practice from a Western perspective. This justifies the need for future research as infant feeding is deeply rooted within religious beliefs and the socio-cultural context.